Introdução à Mecânica Quântica no Ensino Médio através de uma discussão sobre a constante de Planck - Oliveira, Júlio César Gomes (2023)
In this work, we develop an educational product to introduce quantum mechanics in High School through a discussion about Planck's constant. As a learning framework we used David Ausubel's Meaningful Learning Theory (MLT). The product was applied in three meetings for two classes of the second year of high school integrated into the technical course. In the first meeting, a mapping questionnaire was applied in order to raise the students’ prior knowledge related to introductory concepts about Quantum Physics and Planck's constant. In the second meeting, we present a brief historical context about the discovery of Planck's constant and the emergence of Quantum Mechanics. At the end of this meeting, we applied the questionnaire from activity 1. In the third meeting, we carried out an activity to determine Planck's constant using a computational simulator and another using the Arduino platform to automate the collection of experimental data. At the end of this meeting, we applied the questionnaire from activity 2.Through the analysis of the mapping questionnaire, it was possible to identify that a large part of the students in both classes had never heard of Planck's constant and when comparing this questionnaire with the answers from the questionnaires from activities 1 and 2, we noticed a clear evolution in the knowledge acquired by students related to the topic covered in the educational product. Some of the purposes of this work were to contribute to the teaching of Quantum Physics in high schools, in order to make experimentation more accessible, to develop students’ scientific literacy, to combat pseudoscience, and to show students that science is in constant construction. It is hoped that this work can contribute to the area of physics teaching and collaborate for the development of scientific literacy of citizens, in order to promote training so that they can participate assertively in discussions in society involving scientific and technological issues related to Quantum Physics.